PERAMALAN PERGERAKAN LALU LINTAS UDARA DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI MENGGUNAKAN ANALISIS INTERVENSI - WIRYANINGRUM, INDAH LARASATI; SUMARJAYA, I WAYAN; SARI, KARTIKA (E-Jurnal Matematika; Vol 13 No 4 (2024)DO - 10.24843/MTK.2024.v13.i04.p465, 2024)
The aim of this research is to model and forecast air traffic movements at I Gusti Ngurah Rai International Airport that contains an intervention. The intervention analysis consisted of two functions, namely the step function and the pulse function. The step function intervention represents an intervention event that has a long-term effect while the pulse function intervention represents an intervention event that occurs at a certain time. The data before the intervention occurred was modeled using the autoregressive integrated moving average (ARIMA) method which was then continued with intervention analysis. The ARIMA model is used to determine the intervention order b, s, and r. In this study, the pulse function intervention analysis was used to examine data on the number of aircraft at I Gusti Ngurah Rai International Airport, both domestic and international flights in the period January 2013 to July 2020. This research predicts the number of aircraft at the airport for the period August 2020 to December 2020. From results suggest that the ARIMA(2,1,3) model suitable for this air traffic movements with the intervention order , , dan  with MAPE 18,87%.